Targeting NF-kappa B pathway with an IKK2 inhibitor induces inhibition of multiple myeloma cell growth - Jourdan, Michel; Moreaux, Jérôme; Vos, John de; Hose, Dirk; Mahtouk, Karène; Abouladze, Matthieu; Robert, Nicolas; Baudard, Marion; Rème, Thierry; Romanelli, Angela; Goldschmidt, Hartmut; Rossi, Jean-François; et al. (British journal of haematology, 2007)
The pathophysiologic basis for multiple myeloma (MM) has been attributed to the dysregulation of various paracrine or autocrine growth factor loops and to perturbations in several signal transduction pathways including IκB kinase/nuclear factor-κB (IKK/NF-κB). The present study aimed at investigating the effect of a pharmaceutical IKK2 inhibitor, the anilinopyrimidine derivative AS602868, on the in vitro growth of 14 human MM cell lines (HMCL) and primary cells from 13 patients. AS602868 induced a clear dose-dependent inhibition of MM cell growth on both HMCL and primary MM cells, which was the result of a simultaneous induction of apoptosis and inhibition of the cell cycle progression. Combination of AS602868 with suboptimal doses of melphalan or Velcade showed an additive effect in growth inhibition of HMCL. AS602868 also induced apoptosis of primary myeloma cells. Importantly, AS602868 did not alter the survival of other bone marrow mononuclear cells (CD138−) co-cultured with primary MM (CD138+) cells, except for CD34+ haematopoietic stem cells. The results demonstrate the important role of NF-κB in maintaining the survival of MM cells and suggest that a pharmacological inhibition of the NF-κB pathway by the IKK2 inhibitor AS602868 can efficiently kill HMCL and primary myeloma cells and therefore might represent an innovative approach for treating MM patients.
Das Kappa ist im Titel als griechischer Buchstabe dargestellt
Gesehen am 21.01.2022